PATIENT DISCHARGE PROCESS AT X HOSPITAL : FLOW DIFFERENCES, IMPACTS, AND SOLUTION PLANS - Jauhari, Tontowi; Hariyanti, Tita; Suminar Pertiwi, Dian (Universitas Brawijaya, 2025)
Waiting time is one of the factors that affect patient perception of the quality of hospital services, and has an impact on patient satisfaction levels. The process of discharge from hospitalization is one of the factors that can cause low patient satisfaction. The purpose of this paper is to describe various understandings of the discharge process in hospitals X. This study uses qualitative methods. Data collection was carried out through unstructured observations and in-depth interviews with staff regarding the process of discharge of patients from hospitalization. This observation was carried out to observe the process of discharge of patients until the patient received medication using a time-motion study. In-depth interviews were conducted with related units such as inpatient units, inpatient pharmacies, inpatient cashiers, and inpatient registration places. The discharge of insurance patients has a different flow from other payment models. The time to discharge patients with insurance is longer because there is a confirmation process from the inpatient registration unit to the insurance company to get the final guarantee. This process takes an average of about 1 hour and is the longest method of patient discharge. This process involves the inpatient registration unit in charge of contacting the insurance to obtain final financing from the insurance.